Hot melt laminated oriented film

CN116648345BActive Publication Date: 2026-10-27TOYOBO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180078098.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-24
Filing Date
2021-11-11
Publication Date
2026-10-27
Estimated Expiration
2041-11-11

AI Technical Summary

Benefits of technology

[0035]根据本发明,能够提供具有充分的机械特性、湿热环境下的耐久性与层叠界面的密合性高、热粘接时的贴合状态良好的热熔接性层叠取向薄膜、以及将其卷绕而成的卷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004237413520000241
    Figure BDA0004237413520000241
Patent Text Reader

Abstract

Provided are a heat-fusible laminated oriented film having sufficient mechanical properties, durability in a humid heat environment, high adhesion to a laminate interface, and a good bonding state during thermal bonding, and a roll formed by winding the film. The heat-fusible laminated oriented film of the present application has a heat-fusible layer containing a heat-fusible polyolefin resin provided on both surfaces of a base material layer formed from a resin composition containing 99.9 to 60 mass% of a polyamide resin or a polymethylpentene resin and 0.1 to 40 mass% of a modified polyolefin resin, in a manner directly contacting each other by co-extrusion, and is stretched and oriented in at least one direction of a length direction defined as an X axis or a width direction defined as a Y axis, and has a thermal distortion rate at 150°C in both directions of the X axis and the Y axis of 3% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a heat-fusion oriented laminated film having heat-fusion oriented layers on two sides of a substrate layer, and a roll formed by winding the film. Background Technology

[0002] Films and sheets with heat-weldability are laminates in which a heat-weldable layer is disposed on the outermost surface of at least one side of a substrate, so as to bond the heat-weldable layer to an adherend containing resin or metal, for various applications such as packaging and reinforcement. The substrate is selected according to the purpose, but resin substrates are mostly used, and an appropriate resin is selected according to the required properties.

[0003] Furthermore, to achieve excellent adhesion to the adherends, high adhesion is required not only between the adherends and the thermoplastic layer, but also between the substrate and the thermoplastic layer. This is because the areas with the weakest adhesion relative to external stresses that could cause overall peeling are where adhesion is compromised or broken.

[0004] In order to achieve excellent adhesion between the substrate and functional layers such as heat-bonding layers, methods such as corona treatment, plasma treatment to activate the substrate surface, or setting an easy-to-adhere layer on the substrate surface are known.

[0005] For example, Patent Document 1 describes a method for obtaining a strong adhesion to a heat-meltable layer by providing an easy-to-adhere layer containing an acrylic polymer and a crosslinking agent on a substrate, in which it is described that using a polyester resin as the substrate is appropriate.

[0006] Furthermore, Patent Document 2 discloses a method of providing an intermediate layer between the heat-welding layer and the substrate, wherein the resin material for the intermediate layer is described as polypropylene, metallocene polyethylene, and metallocene polypropylene. Additionally, it discloses the use of a polyolefin polymer as the substrate.

[0007] On the other hand, it is known that when the thermally bondable layer and the substrate have high adhesion, a method is used to co-extrude the resins that make up the two layers to manufacture a laminate in which the two layers are in direct contact.

[0008] For example, Patent Document 3 describes a method for manufacturing an unstretched hot-melt laminate by co-extruding a substrate layer and a hot-melt layer in the manufacture of a hot-melt laminate for use in metal laminates.

[0009] Patent document 4 describes a method for extruding and stretching a polypropylene substrate layer and a polyolefin layer with a high melting point on one side and a substrate made of polypropylene film, and then extruding and laminating the polypropylene substrate layer and the polyolefin layer on the substrate side.

[0010] Existing technical documents

[0011] Patent documents

[0012] Patent Document 1: International Publication No. WO2019 / 078134

[0013] Patent Document 2: Japanese Patent Application Publication No. 2017-36354

[0014] Patent Document 3: Japanese Patent No. 6331468

[0015] Patent Document 4: Japanese Patent No. 2530732 Summary of the Invention

[0016] The problem the invention aims to solve

[0017] However, in the invention of Patent Document 1, if polyester is used as the substrate, the carbonyl groups are prone to hydrolysis in harsher humid and hot environments, thus limiting its durability in such environments. Furthermore, the process of setting an easy-to-adhere layer on the substrate becomes complex and costly, a situation also present in Patent Document 2, which uses an intermediate layer.

[0018] In addition, Patent Document 3 discloses a method for producing a film by co-extruding the substrate layer and the hot-melt layer of a hot-melt laminate. However, since it is an unstretched laminate film, its mechanical properties are easily insufficient, and there is also the problem that it is difficult to effectively obtain a larger product area.

[0019] Furthermore, Patent Document 4 discloses a method of stretching after co-extruding two layers, but it further extrudes a heat-fused layer on the substrate side, rather than co-extruding the heat-fused layer together with the substrate layer. Therefore, the adhesion between the heat-fused layer and the substrate layer is prone to inadequacy, and problems can easily arise due to differences in the physical properties of the layers on both sides of the substrate layer. Additionally, in heat-fused laminates stretched after co-extrusion, misalignment of the bonding position can easily occur when thermally bonding the adhered objects. Furthermore, since the substrate is a polypropylene film, its mechanical properties at high temperatures can sometimes become insufficient.

[0020] Therefore, the object of the present invention is to provide a thermoplastic laminated oriented film having sufficient mechanical properties, high durability in humid and hot environments and high adhesion at the laminated interface, and good bonding state during thermal bonding, as well as a roll formed therefrom.

[0021] Solution for solving the problem

[0022] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that by using a resin with high durability in humid and hot environments as a base layer, adding a component that improves the adhesion to the heat-fusion layer, and stretching the heat-fusion layer after co-extruding it on both sides, the above-mentioned problems can be solved, thus completing the present invention.

[0023] That is, the present invention includes the following contents.

[0024] [1] A heat-melting laminated oriented film, wherein a heat-melting layer containing a heat-melting polyolefin resin is disposed on two sides of a substrate layer formed of a resin composition in direct contact by co-extrusion, wherein the resin composition contains 99.9 to 60% by weight of polyamide resin or polymethylpentene resin and 0.1 to 40% by weight of modified polyolefin resin.

[0025] With the length direction defined as the X-axis, the width direction as the Y-axis, and the thickness direction as the Z-axis, stretching orientation was performed at least along one of the X-axis or Y-axis directions.

[0026] The thermal deformation rate at 150℃ is less than 4% in both the X and Y axes.

[0027] [2] According to the thermally weldable laminated oriented thin film of [1], wherein the energy storage modulus at 150°C is 50 MPa or more and the tensile strength is 50 MPa or more in at least one direction of the X-axis or Y-axis.

[0028] [3] According to [1] or [2], the thermally bondable laminated oriented film, wherein the thickness of the thermally bondable layer disposed on both sides is 10 μm or more and 100 μm or less.

[0029] The birefringence difference between the two surfaces of the thermally bondable layer is less than 0.0001.

[0030] [4] A heat-weldable laminated oriented film according to any one of [1] to [3], wherein the orientation is performed by biaxial stretching in two directions along the X-axis and Y-axis, either sequentially or simultaneously.

[0031] [5] A heat-weldable laminated oriented film according to any one of [1] to [4], characterized in that the aforementioned resin composition contains 85 to 65% by mass of polyamide resin and 15 to 35% by mass of modified polypropylene resin, wherein the relative viscosity of the aforementioned polyamide resin measured in 96% sulfuric acid is 2.4 to 3.2, and the acid value of the aforementioned modified polypropylene is 1.0 to 3.5 mg KOH / g.

[0032] [6] The heat-weldable laminated oriented film according to any one of [1] to [5], wherein the aforementioned heat-weldable polyolefin resin is a mixture of multiple polyolefins with a melting peak temperature of 100°C to 165°C as determined by DSC, modified with an anhydride, the anhydride content is 0.1 to 3% by mass, and the MFR is within the range of 1 to 30 g / 10 min when a load of 2.16 kg is applied at 230°C and the extraction amount of a low molecular weight component with a number average molecular weight of 1000 or less using acetone is less than 1% by mass.

[0033] [7] A roll formed by winding along the length direction a thermally bondable laminated oriented film as described in any one of [1] to [6].

[0034] The effects of the invention

[0035] According to the present invention, it is possible to provide a thermoplastic laminated oriented film with sufficient mechanical properties, high durability in humid and hot environments and high adhesion at the laminated interface, good bonding state during thermal bonding, and a roll formed therefrom.

[0036] The detailed reasons are unclear, but the following considerations are made. By using a resin composition containing polyamide resin or polymethylpentene resin and modified polyolefin resin as the substrate layer, durability under humid and hot environments can be improved, and the affinity with the heat-welding layer containing polyolefin resin also becomes good, thus enabling co-extrusion in a direct contact manner. Moreover, by co-extruding the heat-welding layer on both sides of the substrate layer, high adhesion can be obtained at the lamination interface on both sides of the substrate layer due to the wettability and affinity of the heat-welding resin in the molten state. Furthermore, by stretching and oriented the unstretched laminate, not only can productivity be improved, but mechanical properties can also be optimized. In addition, by adjusting the thermal shrinkage characteristics and mechanical strength of the stretched heat-welding laminated film, heat-induced deflection of the substrate layer and wrinkles caused by shrinkage during bonding of the adhered materials can be suppressed, eliminating defects during bonding. Detailed Implementation

[0037] The present invention will now be described in detail. It should be noted that, for ease of explanation, the film-forming direction is sometimes referred to as the mechanical axis direction, longitudinal direction, length direction, or MD direction; and sometimes the direction orthogonal to the film-forming direction and thickness direction is referred to as the width direction, transverse direction, or TD direction. Specifically, in the present invention, the length direction is defined as the X-axis, the width direction as the Y-axis, and the thickness direction as the Z-axis. Furthermore, the various physical properties described in this specification are specifically measured using the methods described in the examples.

[0038] [Thermo-Melt-Bondable Laminated Oriented Films]

[0039] The hot-melt laminated oriented film of the present invention has a hot-melt layer disposed on both sides of a substrate layer formed of a resin composition in a manner that allows direct contact through co-extrusion, and is stretched oriented in at least one direction along the X-axis or Y-axis.

[0040] The confirmation of "setting in a manner of direct contact through co-extrusion" in this invention is based on the determination of the material's structure through the manufacturing method. However, as described below, there are cases where it is impossible or impractical to directly determine the material based on its structure or properties.

[0041] In the case of a three-layer laminated film manufactured by co-extrusion, the adhesion at the lamination interface differs between the first-layer substrate film and the other two layers formed by thermal lamination, indicating a difference in microstructure. Specifically, when observing the molecules at the lamination interface using microstructural analysis, the diffusion and intrusion states of the components in each layer differ, suggesting different adhesion. However, the difference in diffusion is a difference in degree, making it difficult to determine such differences structurally.

[0042] Furthermore, regarding cases where the other two layers are identical, when measuring the birefringence of the two layers, the birefringence is the same in the case of co-extrusion, but slightly different in the case of subsequent hot lamination. However, this only applies to cases where the composition of the two layers is exactly the same; even if the two layers are slightly different, the difference cannot be determined.

[0043] Therefore, it can be said that it is impossible to find statements that define the structure or properties involved in the differences from the prior art, and it is also impossible or impractical to analyze and determine based on the measurement of such structure or properties. Therefore, regarding this invention, at the time of application, there is a situation where it is impossible or substantially impractical to directly determine the substance based on its structure or properties.

[0044] It should be noted that "stretching and orientation" refers to determining the orientation state of the film, which is a commonly used expression in the technical field of this invention.

[0045] The heat-weldable laminated oriented film of the present invention is composed, for example, of a heat-weldable layer / substrate layer / heat-weldable layer, but a protective film, release film, cover film, etc., may also be further provided on at least one outermost surface. Alternatively, it may be provided by pre-heat-welding the adhered materials to one side.

[0046] The following describes the various components of the thermally weldable laminated oriented film of the present invention.

[0047] [Substrate Layer]

[0048] The thermoplastic resin contained in the resin composition constituting the substrate layer can be selected according to the characteristics required by the substrate layer in the target application. However, in order to ensure the durability of the substrate layer itself in harsh humid and hot environments, it is preferable that it does not have functional groups that can become reaction sites for water molecules. In addition, in order to withstand the heat during bonding and the heat of the environment, it is preferable that it has a high melting point.

[0049] Based on the above viewpoints, polyamide resin or polymethylpentene resin is preferably used as the main component of the resin composition in this invention. Furthermore, in order to ensure good dispersibility and adhesion to the heat-welding layer in these resins, the resin composition preferably further contains modified polyolefin resin.

[0050] When the melting point of the thermoplastic resin, which will be the main component of the resin composition, is set to TmS, and the melting point of the resin constituting the heat-welding layer described later is set to TmHS, if the difference between them is defined as ΔT (=TmS-TmHS), it is preferable to combine them in a range of 0-120°C, more preferably 10-100°C. By setting ΔT to 0°C or higher, it is possible to prevent the substrate layer from melting first due to the heat applied during bonding. In addition, by setting ΔT to 120°C or lower, the difference in melt viscosity will not become too large when the resin is melted in an extruder and laminated along the thickness direction, thus suppressing the formation of lamination spots and enabling stable production. From this point of view, it is further preferable that ΔT is 20°C to 90°C, and particularly preferable that ΔT is 40°C to 80°C.

[0051] In order to obtain the strength required for the substrate layer on which the heat-fusion bonding layer is disposed, the thickness of the substrate layer can be 20 μm or more, preferably 25 μm or more, more preferably 35 μm or more, even more preferably 45 μm or more, and preferably 300 μm or less, more preferably 270 μm or less, even more preferably 250 μm or less, and can also be 150 μm or less or 130 μm or less.

[0052] [Polyamide resin]

[0053] When polyamide resins are used as stretched oriented films, the strength of the substrate layer is improved compared to polyolefins, resulting in excellent transportability of the substrate layer. Examples of polyamide resins include aliphatic polyamide resins, aromatic polyamide resins, copolymers of them, or mixtures thereof.

[0054] As for such polyamide resins, there are no particular limitations as long as the polymer has amide bonds (-NHCO-) ​​in the main chain. Examples include polyamide 6 (NY6), polyamide 66 (NY66), polyamide 46 (NY46), polyamide 11 (NY11), polyamide 12 (NY12), polyamide 610 (NY610), polyamide 612 (NY612), poly(m-phenylene adipamide) (MXD6), hexamethylene diamine-terephthalic acid polymer (6T), and hexamethylene diamine-terephthalic acid polymer. Polyamide resins such as methyldiamine-terephthalic acid and adipic acid polymer (66T), hexamethylenediamine-terephthalic acid and ε-caprolactam copolymer (6T / 6), trimethylhexamethylenediamine-terephthalic acid polymer (TMD-T), isophthalic acid-adipic acid and isophthalic acid copolymer (MXD-6 / I), hexamethylenediamine-terephthalic acid and ε-caprolactam copolymer (TMD-T / 6), and diaminodicyclohexylmethane (CA)-isophthalic acid and laurolactam copolymer.

[0055] Among them, from the viewpoint that it is easy to adjust ΔT to the preferred range and that when setting the heat-melting polyolefin in a direct contact manner, it is not easy to generate viscosity difference and stacking spots, aliphatic polyamide resins such as polyamide 6 (NY6), polyamide 66 (NY66), and polyamide 610 (NY610) are preferred.

[0056] As a polyamide resin, a relative viscosity of 2.4 to 3.2 as measured in 96% sulfuric acid is preferred, thereby making it easy to obtain a good viscosity when melt-mixed with a modified polyolefin resin by co-extrusion to obtain a sheet.

[0057] In the resin composition constituting the substrate layer, the content of polyamide resin is preferably 60-99.9% by mass, more preferably 65-95% by mass, further preferably 70-90% by mass, and most preferably 70-85% by mass. Within such a content range, sufficient mechanical strength can be easily obtained, and in addition, based on the volume ratio with modified polyolefin, using polyamide resin as a matrix easily ensures sufficient adhesion.

[0058] [Polymethylpentene resin]

[0059] In addition to homopolymers of polymethylpentene, examples of polymethylpentene resins include copolymers of polyolefins containing 50 mol% or more of methylpentene as monomers, and mixtures thereof. Examples of monomers used in copolymerization include methylene, ethylene, propylene, and butene.

[0060] In the case of polymethylpentene resin, TmS is higher than that of general polypropylene, thus making it easier to ensure ΔT. However, due to its low surface energy, it has low affinity for the heat-welding layer, making it difficult to improve adhesion. Therefore, similar to the case of polyamide resin, a blended modified polyolefin resin is preferred.

[0061] In the resin composition constituting the substrate layer, the content of polymethylpentene resin is preferably 60-99.9% by mass, more preferably 65-95% by mass, further preferably 70-90% by mass, and most preferably 70-85% by mass. Within such a content range, the improved heat resistance effect produced by polymethylpentene is easily obtained. In addition, based on the volume ratio with the modified polyolefin, using polymethylpentene resin as a matrix easily ensures sufficient adhesion.

[0062] [Modified polyolefin resin]

[0063] Polyolefins excel in lacking functional groups that can react with water molecules. Furthermore, since the heat-sealing layer is composed of modified polyolefins, it exhibits high affinity and excellent adhesion in co-extrusion processes. Additionally, the dispersibility in polyamide resins or polymethylpentene resins is improved by using modified polyolefin resins.

[0064] Examples of modified polyolefin resins include those modified from the following polyolefin resins. In this specification, "modified" means containing structural units different from those in polyolefins within the same molecule. Examples of polyolefin resins to be modified include high-density polyethylene, low-density polyethylene, ultra-high molecular weight polyethylene, linear low-density polyethylene, polypropylene, poly(1-butene), and poly(4-methylpentene). Mixtures of these polyolefin resins or copolymers containing them as components are also possible examples. Polypropylene is particularly preferred among these polyolefin resins.

[0065] Especially when mixed with polyamide resin via melt blending, the modified polyolefin resin preferably has functional groups that react with the terminal groups and / or main chain amide groups of the polyamide resin. Specifically, it is preferable to have modified polyolefin resins with carboxylic acid groups, anhydride groups, epoxy groups, oxazoline groups, amino groups, isocyanate groups, etc., and more preferably with anhydride groups. The same modified polyolefin resin can also be used when mixed with polymethylpentene resin, but from the viewpoint of compatibility, maleic acid modified polypropylene resin is preferred. It should be noted that graft modification and copolymerization can be used as modification methods.

[0066] Specific examples of modified polyolefin resins include, for instance, maleic anhydride-modified polyethylene, maleic anhydride-modified polypropylene, ethylene / acrylic acid copolymers, ethylene / methacrylic acid copolymers, and copolymers in which part or all of the carboxylic acid portion is formed into salts of sodium, lithium, potassium, zinc, and calcium; ethylene / methyl acrylate copolymers, ethylene / ethyl acrylate copolymers, ethylene / methyl methacrylate copolymers, ethylene / ethyl methacrylate copolymers, and ethylene / ethyl acrylate-g-maleic anhydride copolymers (where "-g-" indicates grafting). (The same applies below), ethylene / methyl methacrylate-g-maleic anhydride copolymer, ethylene / propylene-g-maleic anhydride copolymer, ethylene / butene-1-g-maleic anhydride copolymer, ethylene / propylene / 1,4-hexadiene-g-maleic anhydride copolymer, ethylene / propylene / dicyclopentadiene-g-maleic anhydride copolymer, ethylene / propylene / 2,5-norbornene-g-maleic anhydride copolymer, hydrogenated styrene / butadiene / styrene-g-maleic anhydride copolymer, hydrogenated styrene / isoprene / styrene-g-maleic anhydride copolymer, etc. Among them, maleic acid-modified polypropylene or ethylene-propylene copolymers are particularly preferred.

[0067] From the viewpoint of dispersibility in polyamide resins, the acid value of modified polypropylene is preferably 1.0 to 3.5 mg KOH / g, more preferably 1.5 to 3.0 mg KOH / g.

[0068] To improve the affinity with the heat-welding layer or reduce the moisture content of the substrate layer, the content of the modified polyolefin resin can be appropriately adjusted, but it is preferably 0.1-40% by mass, more preferably 5-35% by mass, even more preferably 10-35% by mass, and even more preferably 15-35% by mass in the resin composition constituting the substrate layer.

[0069] [Any other components of the substrate layer]

[0070] The resin composition constituting the substrate layer may contain other resin components that are compatible with polyamide resin and / or polymethylpentene resin, provided that this does not impair the purpose of the present invention.

[0071] Furthermore, without prejudice to the purpose of this invention, appropriate fillers may be included as needed for purposes such as improving slip properties. As such fillers, substances known to have been used as slip-improving agents for films and sheets can be used, such as calcium carbonate, calcium oxide, alumina, kaolin, silicon oxide, zinc oxide, carbon black, silicon carbide, tin oxide, cross-linked acrylic resin particles, cross-linked polystyrene resin particles, melamine resin particles, and cross-linked silicone resin particles. Furthermore, colorants, antistatic agents, antioxidants, organic lubricants, catalysts, etc., may be appropriately added to the substrate layer.

[0072] In addition, as other arbitrary components, various additives that have been used in polyamide resins, polymethylpentene resins, and modified polyolefin resins can be cited. Such additives include stabilizers, impact modifiers, flame retardants, release agents, slip modifiers, colorants, plasticizers, and nucleating agents. Furthermore, components that react with the end groups of the polyamide resin may also be included.

[0073] As another arbitrary component, for example, 0.001-10% by mass may be used in the resin composition.

[0074] [Thermo-fusion bonding layer]

[0075] Since the heat-welding layer also needs to be hygrothermal durable and have adhesive strength to the adhered objects, a heat-welding polyolefin resin is included. The heat-welding layer is disposed on both sides of the substrate layer as described above. It should be noted that, in this specification, "heat-welding" refers to the property of being able to be fused to the adhered objects by heating, preferably the property of being able to be fused to SUS316, which is a metal, by heating.

[0076] The heat-fusion bonding layers provided on the two surfaces can have the same composition or different compositions. For example, when bonding objects made of the same material to each other, it is preferable to provide heat-fusion bonding layers with the same composition on both surfaces. In addition, the thickness of the heat-fusion bonding layers can be the same or different, but in the case described above, it is preferable to provide heat-fusion bonding layers with the same thickness on both surfaces.

[0077] The thickness of the heat-welding layer is preferably 100 μm or less. While a strong bond can be achieved between the heat-welding layer and the substrate layer formed by co-extrusion, for example, when using acid-modified polyolefin resins, the acid-modified portion has functional groups that are affected by moisture. Therefore, if the layer is unnecessarily thickened, it tends to become brittle and break under harsh humid and hot environments. For the above reasons, the thickness of the heat-welding layer is preferably 90 μm or less, more preferably 80 μm or less, further preferably 75 μm or less, and particularly preferably 60 μm or less. Furthermore, excessive thinness weakens the mechanical mitigation function of the heat-welding layer in the thickness direction; therefore, it is preferably, for example, 10 μm or more, more preferably 15 μm or more, and particularly preferably 20 μm or more.

[0078] The heat-welding layer is provided in a manner that allows it to directly contact both sides of the substrate layer through co-extrusion. This ensures that the lamination interface state of the two sides of the substrate layer is identical on both sides. Consequently, when heat-welding layers of identical composition are provided, the difference in birefringence between the two sides of the heat-welding layer is less than 0.0001, which is preferable in terms of improving the adhesion of the lamination interface between the two sides.

[0079] [Thermo-melting polyolefin resin]

[0080] As a polyolefin resin with heat-melting properties, unmodified polyolefin resins can also be used, but modified polyolefins are preferred, and modified polyolefins containing polypropylene are particularly preferred.

[0081] Examples of unmodified polyolefin resins include homopolymers and copolymers of olefins with 2 to 8 carbon atoms, and copolymers of olefins with 2 to 8 carbon atoms with other monomers. Specifically, examples include: high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene resin, etc.; polyethylene, polypropylene, polyisobutylene, poly(1-butene), poly(4-methylpentene), polyvinylcyclohexane, polystyrene, poly(p-methylstyrene), poly(α-methylstyrene), ethylene-propylene block copolymers, ethylene-propylene random copolymers, ethylene-butene-1 copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-butene-propylene terpolymers, ethylene-propylene diene rubber, ethylene-hexene copolymers, etc. (α-olefin copolymers), ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-methyl methacrylate copolymers, ethylene-vinyl acetate-methyl methacrylate copolymers, polybutadiene-styrene copolymers, polybutadiene-maleic anhydride copolymers, and ionic resins. Furthermore, chlorinated polyolefins obtained by chlorinating these polyolefins can also be used.

[0082] As described above, various types of heat-melting polyolefin resins can be used, with modified polyolefin resins incorporating various functional groups, such as carboxyl and hydroxyl groups, being particularly preferred.

[0083] Furthermore, among these modified polyolefin resins, from the perspective of improving the adhesion to the metal layer and the excellent resistance to electrolytes, modified polyolefin resins with an acid value of 1 to 200 mg KOH / g (also known as acid-modified polyolefin resins) and / or modified polyolefin resins with a hydroxyl value of 1 to 200 mg KOH / g (also known as hydroxyl-modified polyolefin resins) can be used.

[0084] Acid-modified polyolefin resins refer to polyolefin resins containing carboxyl groups and carboxylic anhydride groups in their molecules. They are synthesized by modifying polyolefins with unsaturated carboxylic acids or their derivatives. Grafting modification and copolymerization can be used as modification methods.

[0085] Acid-modified polyolefin resin is a graft-modified polyolefin obtained by grafting or copolymerizing at least one polymerizable olefinic unsaturated carboxylic acid or its derivative onto a polyolefin resin before modification.

[0086] Examples of polyolefin resins before modification include the aforementioned polyolefin resins, among which homopolymers of propylene, copolymers of propylene and α-olefins, homopolymers of ethylene, and copolymers of ethylene and α-olefins are preferred. One of these resins may be used alone, or two or more may be used in combination.

[0087] Examples of acid-modified polyolefin resins include maleic anhydride-modified polypropylene, ethylene-(meth)acrylic acid copolymer, ethylene-acrylate-maleic anhydride terpolymer, or ethylene-methacrylate-maleic anhydride terpolymer. Specifically, commercially available resins include "MODIC" manufactured by Mitsubishi Chemical Corporation, "ADMER" and "UNISTOLE" manufactured by Mitsui Chemicals Corporation, "TOYO-TAC" manufactured by Toyobo Corporation, "UMEX" manufactured by Sanyo Chemicals Corporation, "REXPEARL EAA" and "REXPEARL ET" manufactured by Japan Polyethylene Corporation, "PRIMACOR" manufactured by Dow Chemical Company, "NUCREL" manufactured by Dow-Mitsui Polychemiscals, and "BONDINE" manufactured by ARKEMA.

[0088] Hydroxyl-modified polyolefin resins are polyolefin resins containing hydroxyl groups in their molecules, synthesized by grafting or copolymerizing the polyolefin with hydroxyl-containing (meth)acrylates or hydroxyl-containing vinyl ethers (described later). Examples of the aforementioned hydroxyl-containing (meth)acrylates include hydroxyethyl (meth)acrylate; hydroxypropyl (meth)acrylate; glyceryl (meth)acrylate; lactone-modified hydroxyethyl (meth)acrylate; polyethylene glycol (meth)acrylate; and polypropylene glycol (meth)acrylate. Examples of the aforementioned hydroxyl-containing vinyl ethers include 2-hydroxyethyl vinyl ether; diethylene glycol monovinyl ether; and 4-hydroxybutyl vinyl ether.

[0089] The preferred hot-melt-bonding polyolefin resin is one that has been modified by mixing polyolefins with a melting peak temperature of 100°C-165°C as determined by DSC using anhydride, wherein the anhydride content is 0.1-3% by mass, and the MFR is measured to be 1-30 g / 10 min under a load of 2.16 kg at 230°C, and the extraction amount of low molecular weight components with a number average molecular weight of less than 1000 using acetone is less than 1% by mass.

[0090] [Any other components of the heat-fusion bonding layer]

[0091] Provided that the purpose of this invention is not compromised, the heat-welding layer may contain other resin components that are compatible with the heat-welding polyolefin resin.

[0092] The heat-fusion layer may also be composed of resin alone, but it may also contain additives such as adhesive agents, antistatic agents, antioxidants, metal passivators, dehydrating agents, acid adsorbents, etc., or crosslinking agents, chain transfer agents, nucleating agents, lubricants, plasticizers, fillers, reinforcing materials, pigments, dyes, flame retardants, etc., without impairing the effect of the present invention.

[0093] [Characteristics of thermally weldable laminated oriented films]

[0094] The heat-weldable laminated oriented film of the present invention preferably has a heat deformation rate of 4% or less at 150°C in both the X and Y axes. If the heat deformation rate at 150°C is 4% or less, the bonding state during heat welding is more easily achieved. From this viewpoint, a heat deformation rate at 150°C is more preferably 3% or less, and even more preferably 2.5% or less. A lower heat deformation rate at 150°C is more preferred; the most preferred lower limit for the heat deformation rate at 150°C is 0%, but 1% or more is also preferred.

[0095] Furthermore, the energy storage modulus at 150°C is preferably 50 MPa or more in at least one direction of the X-axis or Y-axis, and more preferably 50 MPa or more in both the X-axis and Y-axis directions. When the energy storage modulus at 150°C is 50 MPa or more, the deformation caused by stress during thermal bonding is smaller, and the bonding state tends to improve. From this point of view, the energy storage modulus at 150°C is preferably 70 MPa or more, more preferably 100 MPa or more, and the larger the energy storage modulus at 150°C, the better. As a realistic upper limit, it is around 500 MPa.

[0096] Furthermore, the fracture strength at room temperature (25°C) is preferably 50 MPa or higher in at least one direction of the X-axis or Y-axis, and more preferably 50 MPa or higher in both the X-axis and Y-axis directions. When the fracture strength is 50 MPa or higher, the workability during thermal bonding becomes better, and there is a tendency for damage to the lamination interface to occur. From this point of view, the fracture strength is preferably 70 MPa or higher, more preferably 100 MPa or higher, and the higher the fracture strength, the better. As a realistic upper limit, it is around 500 MPa.

[0097] Furthermore, the elongation at break retention rate after treatment with saturated water vapor at 121°C and two atmospheres for 200 hours in at least one direction of the X-axis or Y-axis is preferably 50% or more, and more preferably 50% or more in both the X-axis and Y-axis directions. If the elongation at break retention rate is 50% or more after treatment with saturated water vapor at 121°C and two atmospheres for 200 hours, sufficient durability can be achieved even in harsher humid and hot environments than before.

[0098] [Method for manufacturing thermally bondable laminated oriented thin films]

[0099] The following describes the case where polyamide resin is used as the main component of the resin constituting the substrate layer. It should be noted that the following method can also be used when forming the substrate layer if polymethylpentene resin is used.

[0100] The heat-weldable laminated oriented film of the present invention can be manufactured, for example, by mixing the materials constituting each layer, co-extruding the mixture, molding the unstretched laminate, stretching it, heat treatment, etc.

[0101] There are no particular limitations on the method of mixing and compounding polyamide resin with modified polyolefin resin, and then with other arbitrary components. For example, a single-screw extruder, a twin-screw extruder, a pressure kneader, or a Banbury mixer can be used. Among these, a twin-screw extruder is particularly preferred. The operating conditions of the twin-screw extruder vary depending on the type of polyamide resin, the type and amount of each component, and so on. However, for example, relative to the melting point Tm of the thermoplastic resin, i.e., the polyamide resin, which is the main component, the operating temperature can be set to around +25°C. The screw configuration of the extruder is preferably equipped with several kneading discs that provide excellent mixing.

[0102] The resin composition constituting the substrate layer is co-extruded together with a heat-bonding layer into a sheet, and then cooled and cured by a casting drum to obtain an unstretched laminated film. The unstretched laminated film is stretched at least along one of the X-axis or Y-axis directions, but biaxial stretching is preferred.

[0103] In the case of biaxial stretching, the unstretched laminated film is stretched once or twice or more in the length direction (X-axis) at Tg to (Tg+100)℃ to achieve a total multiplication factor of 2 to 6 times, and stretched once or twice or more in the width direction (Y-axis) at Tg+20 to (Tg+100)℃ to achieve a total multiplication factor of 3 to 7 times. Here, Tg represents the glass transition temperature of the thermoplastic resin that becomes the main component.

[0104] Depending on the requirements, a heat treatment of 1 to 60 seconds can be performed at Tm-60 to Tm-5℃, followed by shrinkage of 0 to 20% in the width direction at a temperature 10 to 20℃ lower than the heat treatment temperature, and then reheat treatment. Furthermore, the above stretching can be sequential biaxial stretching or simultaneous biaxial stretching, and the stretching sequence can be transverse-longitudinal.

[0105] The present invention is characterized in that the heat-fusion bonding layer is formed together with the substrate layer by co-extrusion. In conventional methods, the heat-fusion bonding layer is set by methods such as dry lamination and wet lamination as lamination methods, and extrusion resin coating, melt resin coating, and liquid coating as coating methods. However, these methods require the stacking of substrate layers with a specific width in the width direction. Therefore, once the substrate layer is pre-manufactured, the heat-fusion bonding layer needs to be set by other processes. Consequently, due to the limitation of this width, the area that can be produced per unit time is often limited.

[0106] In this invention, in order to establish a heat-welding layer, when extruding the resin using co-extrusion, it is preferable to adjust the melt temperature appropriately according to the viscosity of the substrate layer during melt extrusion. Furthermore, the type and molecular weight of the polyolefin resin can be selected to make the melt viscosity of the heat-welding resin layer appropriate.

[0107] The operating temperature (melting temperature) of the extruder used as the heat-welding layer is preferably TmHS+20℃~TmHS+120℃, more preferably TmHS+50℃~TmHS+100℃, relative to the melting point TmHS of the polyolefin resin.

[0108] The discharge rate of the molten material from the heat-welding layer of the extruder is appropriately determined based on factors such as the thickness ratio relative to the substrate layer, the thickness of the laminate, and the production line speed.

[0109] [roll]

[0110] The roll of the present invention is formed by winding the above-described heat-weldable laminated oriented film in the length direction. That is, the heat-weldable laminated oriented film of the present invention is preferably manufactured continuously.

[0111] [use]

[0112] The thermally bondable laminated oriented film of the present invention can be used for thermal bonding of various substrates. Examples of substrates include various metals, various resins, fiber-reinforced resins containing glass fibers, ceramics, etc. Examples of substrate shapes include, in addition to sheets, films, and plates, three-dimensional shapes having planar portions and curved surfaces that bend the planar portion.

[0113] The thermal bonding of thermo-meltable laminated oriented films is performed above the temperature at which the thermo-meltable layer softens. In addition, when thermal bonding is performed at a temperature at which the substrate layer undergoes thermal deformation, thermal bonding can also be performed on substrates with more complex surface shapes.

[0114] Example

[0115] The present invention will be described in more detail below with examples and comparative examples. It should be noted that in the present invention, physical properties are measured or evaluated by the following methods. Unless otherwise specified, "parts" refers to "parts by mass" and "%" refers to "% by mass".

[0116] (1) Thickness of the film and each layer

[0117] The film was cut using a slicing machine to obtain a cross-section perpendicular to the film surface. A platinum-palladium alloy coated onto this cross-section by sputtering was used as the observation sample. The film cross-section was observed using a scanning electron microscope (Hitachi, S-510 type), and photographs were taken at an appropriate magnification with the total film thickness as one field of view. Based on the images, the thickness of each layer was measured using a scale. The thickness of three independently prepared cross-sectional samples was measured, and the average value was taken as the layer thickness of the laminated film.

[0118] (2) Birefringence of the thermally fused layer, front-back difference

[0119] With the length direction defined as the X-axis, the width direction as the Y-axis, and the thickness direction as the Z-axis, a sample piece is cut and positioned on a polarizing microscope so that the XY cross-section (End direction) can be observed. A prescribed detection plate is set on the polarizing microscope, and using the Senarmont method, the birefringence in the thickness direction of each surface layer of the thermally bonded layer is measured based on the observed phase difference and the sample thickness. The difference is then calculated as the front-to-back birefringence difference of the thermally bonded layer.

[0120] (3) The difference in melting point between the front and back sides of the heat-fusion layer

[0121] For the melting point of the outermost heat-fused layer of the sample piece, 10 mg of sample was taken from each surface and measured using DSC (Q100 manufactured by TAinstrument) at a heating rate of 10 °C / min. The endothermic peak representing the melting point was defined as the melting point and the absolute value of the difference between the front and back sides was calculated.

[0122] (4) Fracture strength

[0123] Specimens with a width of 10 mm and a length of 100 mm were cut out. Tensile testing machine (TENSILON UCT-100 model manufactured by ORIENTEC CO.,LTD.) was used to determine the strength at the fracture point as the fracture strength at room temperature (25°C) based on JIS-K7127.

[0124] (5) Heat distortion rate at 150℃

[0125] With the length direction defined as the X-axis, the width direction as the Y-axis, and the thickness direction as the Z-axis, samples were taken in the XY plane of the specimen at 200mm × 200mm intervals to create markings (distance between markings: 100mm). Then, without applying tension, the specimen was treated in a constant temperature bath set to 150℃ for 30 seconds, and the distance between the markings was measured. Using the distance between the markings before heat treatment as a reference, the heat deformation rate at 150℃ was calculated based on the change in the distance between the markings.

[0126] (6) Energy storage modulus at 150℃

[0127] With the length direction defined as the X-axis, the width direction as the Y-axis, and the thickness direction as the Z-axis, samples were taken along the X and Y directions with a length of 40 mm (width of 5 mm). A dynamic viscoelasticity measuring device (Perkin Elmer Co., Ltd. DMA8000) was used, with a clamping distance of 10 mm, a displacement of 0.01 mm, a frequency of 1 Hz, and a temperature rise from room temperature to 180 °C at 2 °C / min. The storage modulus was measured and the value was read at 150 °C.

[0128] (7) Fit

[0129] (7-1) Interface 1: Thermo-weld layer - substrate layer

[0130] Cut specimens with a width of 25 mm and a length of 150 mm. Peel the end of the heat-fused layer from the substrate layer to create the peel initiation point. Using a tensile testing machine (ORIENTEC Co., Ltd. TENSILON UCT-100 model), perform a 180° peel at a peel speed of 100 mm / min according to JIS-C2151. Perform five measurements, and evaluate the average of the maximum values ​​from each measurement as the peel force, based on the following criteria.

[0131] A: The peeling force is above 15N or the adhesion is strong and the peeling end cannot be made.

[0132] B: Peel strength is 5N or higher and less than 15N

[0133] C: Peeling force less than 5N

[0134] (7-2) Interface 2: Thermo-fusible layer - Adhesive

[0135] The adhesion of interface 2 was evaluated using SUS316 and polypropylene sheets as substrates. The method for preparing interface 2 is as follows: Two SUS316 or polypropylene sheets, cut to 150 mm² using a press, were prepared. The resulting heat-fused laminated oriented film was sandwiched between them. For positioning, a 5 mm diameter hole was punched at the determined location. After confirming there was no misalignment, the sheets were bonded at 160°C and 5 MPa for 1 minute.

[0136] Cut out a molded sample with a width of 10 mm and a length of 100 mm. Peel off the end of the adhered material to be tested for adhesion to form the peel start. Use a tensile testing machine (TENSILON UCT-100 model manufactured by ORIENTEC Co., Ltd.) to perform 180° peeling at a peeling speed of 100 mm / min according to JIS-C2151. The test is performed 5 times. The average value of the maximum values ​​of each test is evaluated as the peel force based on the following criteria.

[0137] A: Peeling force is above 10N

[0138] B: Peel strength is 3N or higher and less than 10N

[0139] C: Peeling force less than 3N

[0140] In addition, during lamination, if the dimensions of the thermoplastic laminated oriented film change, resulting in seepage or shrinkage from the SUS316 and polypropylene sheets on both sides, and if misalignment is observed in the positioning perforations, the following criteria will be used to evaluate the quality of the lamination.

[0141] 〇: The perforation is not misaligned and fits well.

[0142] ×: The perforation is misaligned and the fit is poor.

[0143] (7-3) Sealing performance under hot and humid conditions (121℃×48 hours)

[0144] The SUS316 adherent sample prepared in (7-2) above was immersed in water at 121°C for 48 hours and then dried at room temperature for 24 hours. The sample obtained therefrom was then evaluated according to the following criteria, except that it was carried out in the same manner as (7-2) above.

[0145] A: Peeling force is above 10N

[0146] B: Peel strength is 3N or higher and less than 10N

[0147] C: Peeling force less than 3N

[0148] (8) Relative viscosity of polyamide resin

[0149] The concentration of polyamide resin was determined using an Ubbelohde viscometer at 25°C with 96% sulfuric acid solution at a concentration of 1 g / dl.

[0150] (9) Acid value of modified polyolefin resin

[0151] The acid value (mgKOH / g) of modified polyolefin resin is the amount of KOH required to neutralize 1g of acid-modified polyolefin, and is determined according to the test method of JIS K0070 (1992). Specifically, 1g of acid-modified polyolefin is dissolved in 100g of xylene at a temperature adjusted to 100°C, and titrated with 0.1mol / L potassium hydroxide ethanol solution [trade name "0.1mol / L ethanolic potassium hydroxide solution", manufactured by Wako Pure Chemical Industries, Ltd.] at the same temperature using phenolphthalein as an indicator. The amount of potassium hydroxide required for titration is then converted to mg to calculate the acid value (mgKOH / g).

[0152] (10) Melting peak temperature of polyolefins

[0153] Based on the difference in melting point between the front and back sides of the heat-fusion layer mentioned above (3), the melting peak temperature of the polyolefin is determined.

[0154] (11) Melt Flow Rate (MFR)

[0155] Using an extrusion-type plasticizer as specified in JIS K6760, a load of 2.16 kg was applied at 230°C, and the determination was performed using the method specified in JIS K7210 (unit: g / 10 min).

[0156] (12) Extraction amount of low molecular weight components

[0157] Acetone was evaporated and cooled in a 90°C water bath, and Soxhlet extraction was performed for 2 hours to extract the dissolved components. The resulting solution was used to confirm the low molecular weight components with a number average molecular weight of less than 1000 using an apparatus (Waters Corporation e2695). The extraction yield (mass%) of the low molecular weight components was determined from the mass of the sample.

[0158] [Example 1]

[0159] Resin A was used as the resin composition constituting the substrate layer. Resin A contained 70% by mass of 6-nylon (PA6) (T-803 manufactured by Toyobo Co., Ltd., relative viscosity 2.7) and 30% by mass of modified polypropylene (PO) (acid value 2.8 mgKOH / g, MMP-006 manufactured by Priman Polymer Co., Ltd.). Resin A was fed into an extruder and melt-blended at a melt temperature of 260°C. While extruding from the die slit, a heat-welding modified polyolefin resin (TOYO-TAC M100, anhydride content of 1% by mass, melt peak temperatures of 110°C and 126°C, MFR of 10 g / 10 min, low molecular weight component extraction of 0.5% by mass) was melt-blended on both sides through the extruder at a melt temperature of 230°C in direct contact with the substrate layer. The mixture was co-extruded through the die slit and cooled and cured on a casting drum set to a surface temperature of 25°C to produce an unstretched film. At this point, the ejection amount is controlled to achieve a thickness ratio of 1:3:1 for the unstretched film, and co-extrusion is performed.

[0160] The unstretched film was fed into a roller assembly heated to 70°C and stretched 3.0 times along its length. It was then cooled with a roller assembly at 25°C. The film was then held at both ends with clamps and fed into a tenter frame, where it was stretched 4.0 times laterally in an atmosphere heated to 90°C. Next, it was heat-fixed at 180°C in the tenter frame and relaxed by 5% in the width direction before being uniformly and slowly cooled to room temperature to obtain a biaxially stretched film with a thickness of 125 μm. This film was then wound into a roll, thus obtaining a roll of thermally fused laminated oriented film. The characteristics of the obtained thermally fused laminated oriented film are summarized in Table 1.

[0161] [Example 2]

[0162] As the resin composition constituting the substrate layer, resin B is used, containing 70% by mass of polymethylpentene (TPX) (manufactured by Mitsui Chemicals, Ltd., DX845) and 30% by mass of modified polypropylene (the same substances contained in resin A). Resin B is fed into an extruder and melt-blended at a melt temperature of 260°C. Simultaneously, a heat-welding modified polyolefin resin (manufactured by Toyobo Co., Ltd., TOYO-TAC M100) is fed into the extruder on both sides in direct contact with the substrate layer and melt-blended at a melt temperature of 230°C. Co-extrusion is then performed through a die slit, and the mixture is cooled and solidified on a casting drum set to a surface temperature of 25°C to produce an unstretched film. The ejection rate is controlled to achieve a thickness ratio of 1:3:1 for the unstretched film during co-extrusion.

[0163] The unstretched film was fed into a roller assembly heated to 100°C and stretched 3.5 times along its length. It was then cooled using a roller assembly at 25°C. The two ends of the film were then held by clamps and fed into a tenter frame. The film was stretched 4.0 times laterally in an atmosphere heated to 110°C. It was then heat-fixed at 200°C in the tenter frame and relaxed by 5% in the width direction. After that, it was uniformly and slowly cooled to room temperature to obtain a biaxially stretched film with a thickness of 125 μm. The film was then wound into a roll to obtain a roll of thermally fused laminated oriented film. The characteristics of the obtained thermally fused laminated oriented film are summarized in Table 1.

[0164] [Example 3]

[0165] In Example 1, a biaxially stretched film with a thickness of 250 μm was obtained by changing the amount of resin A and the amount of modified polyolefin resin ejected. Otherwise, the same procedure as in Example 1 was followed to obtain a roll of thermally fusible laminated oriented film. The characteristics of the obtained thermally fusible laminated oriented film are summarized in Table 1.

[0166] [Example 4]

[0167] In Example 2, by varying the ejection amounts of resin B and the modified polyolefin resin, a biaxially stretched film with a thickness of 250 μm was obtained. Otherwise, the procedure was the same as in Example 2 to obtain rolls of thermally fusible laminated oriented films. The characteristics of the obtained thermally fusible laminated oriented films are summarized in Table 1.

[0168] [Example 5]

[0169] In Example 1, the contents of each resin in resin A were changed as shown in Table 1. Otherwise, the procedure was the same as in Example 1 to obtain a roll of thermally bondable laminated oriented film. The characteristics of the obtained thermally bondable laminated oriented film are summarized in Table 1.

[0170] [Example 6]

[0171] In Example 1, the 6 nylon in resin A was replaced with 610 nylon (PA610) (made by ARKEMA, HIPROLON 7ONN, relative viscosity 2.7). Otherwise, the procedure was the same as in Example 1 to obtain rolls of thermally bondable laminated oriented films. The properties of the obtained thermally bondable laminated oriented films are summarized in Table 1.

[0172] [Example 7]

[0173] In Example 1, the modified polyolefin resin with heat-melting properties was changed to TOYO-TAC M312 (anhydride content of 1.0% by mass, melt peak temperatures of 110°C and 130°C, MFR of 12 g / 10 min, and low molecular weight component extraction of 0.8% by mass). Otherwise, the procedure was the same as in Example 1 to obtain rolls of heat-melting laminated oriented films. The characteristics of the obtained heat-melting laminated oriented films are summarized in Table 1.

[0174] [Example 8]

[0175] In Example 1, the modified polyolefin resin in resin A was changed to TOYO-TAC M-100. Otherwise, the procedure was the same as in Example 1 to obtain a roll of thermally bondable laminated oriented film. The properties of the obtained thermally bondable laminated oriented film are summarized in Table 1.

[0176] [Comparative Example 1]

[0177] A heat-fusion laminated oriented film having the same layer composition as the heat-fusion laminated oriented film obtained in Example 1 is prepared using the method described below.

[0178] Specifically, resin A is fed into an extruder and melt-blended at a melting temperature of 260°C. While being extruded from a die slit, it is simultaneously cooled and solidified on a casting drum set to a surface temperature of 25°C to form an unstretched film. This unstretched film is then fed into a roller assembly heated to 70°C and stretched 3.0 times along its length, followed by cooling with rollers at 25°C. The film is then held at both ends with clamps and fed into a tenter frame, where it is stretched 4.0 times laterally in an atmosphere heated to 90°C. It is then heat-fixed at 180°C in the tenter frame, relaxed by 5% in the width direction, and then uniformly and slowly cooled to room temperature to obtain a biaxially stretched film with a thickness of 75 μm. This film is then wound into a roll, and roll A1 of the film consisting only of the substrate layer is collected.

[0179] In addition, a modified polyolefin resin (manufactured by Toyobo Co., Ltd., TOYO-TAC M100) with heat-welding properties is fed into an extruder and cooled and cured on a casting drum with a surface temperature set at 25°C to produce roll A2 of unstretched film.

[0180] Roll A1, which becomes the substrate layer, is output as roll A2, which is then output with one side attached. A heating roller wound with Teflon tubing is set to 160°C, and lamination is performed while clamping, resulting in a single-sided laminated roll A3. Then, single-sided laminated roll A3 is output with roll A2 attached to the substrate layer side, and lamination is performed while clamping, yielding a roll of thermally bondable laminated oriented film. The characteristics of the thermally bondable laminated oriented film obtained by this method are summarized in Table 1.

[0181] [Comparative Example 2]

[0182] Resin A is fed into an extruder and melt-blended at a melt temperature of 260°C. Simultaneously, a heat-welding modified polyolefin resin (manufactured by Toyobo Co., Ltd., TOYO-TAC M100) is fed into the extruder on one side, directly contacting the substrate layer, and melt-blended at a melt temperature of 230°C. Co-extrusion is then performed through the die slit and cooled and cured on a casting drum set to a surface temperature of 25°C to produce an unstretched film. The extrusion volume is controlled to maintain a thickness ratio of 1:3 for the unstretched film. The unstretched film is then fed into a roller assembly heated to 70°C and stretched 3.0 times along its length, followed by cooling with rollers at 25°C. The film is then held at both ends by clamps and fed into a tenter frame, where it is stretched 4.0 times laterally in an atmosphere heated to 90°C. Then, while being heat-fixed at 180°C in a tenter frame, the film is relaxed by 5% in the width direction and then slowly cooled to room temperature to obtain a biaxially stretched film with a thickness of 100μm. The film is then wound into a roll to produce a single-sided laminated roll A4.

[0183] In addition, a modified polyolefin resin (manufactured by Mitsui Chemicals Co., Ltd., ADMER QE840) with heat-welding properties is fed into an extruder and cooled and cured on a casting drum with a surface temperature set at 25°C to produce unstretched films and unstretched film rolls A5.

[0184] Output roll A4, and output roll A5 in a manner that adheres to the substrate layer side. Set the heating roller wound with Teflon tubing to 160°C, and perform lamination while clamping to obtain a roll of thermally bondable laminated oriented film. The characteristics of the thermally bondable laminated oriented film obtained by this method are summarized in Table 1.

[0185] [Comparative Example 3]

[0186] Resin B was fed into an extruder and melt-blended at a melt temperature of 260°C. Simultaneously, a heat-welding modified polyolefin resin (manufactured by Toyobo Co., Ltd., TOYO-TAC M100) was fed into the extruder on both sides in direct contact with the substrate layer and melt-blended at a melt temperature of 230°C. Co-extrusion was then performed through the die slit, and the resin was cooled and solidified on a casting drum set to a surface temperature of 25°C to produce an unstretched film. The ejection rate was controlled to maintain a thickness ratio of 1:3:1 for the unstretched film, resulting in a 125 μm thick unstretched film. This film was then wound into rolls, thus collecting rolls of heat-welding laminated oriented films. The characteristics of the obtained heat-welding laminated oriented films are summarized in Table 1.

[0187] [Comparative Example 4]

[0188] Resin C, made from polyethylene 2,6-naphthalenedicarboxylate with an intrinsic viscosity of 0.60 dl / g (35°C, o-chlorophenol), was fed into an extruder and melt-blended at a melt temperature of 300°C. While extruding from a die slit, the resin was cooled and solidified on a casting drum set to a surface temperature of 60°C to produce an unstretched film. This unstretched film was fed into a roller assembly heated to 125°C and stretched 3.5 times along its length, then cooled with rollers at 25°C. The ends of the film were then held in clamps and fed into a tenter frame, where it was stretched 4.0 times laterally in an atmosphere heated to 145°C. Then, while heat-fixing at 225°C in the tenter frame, the film was relaxed by 5% in the width direction and then uniformly and slowly cooled to room temperature to obtain a biaxially stretched film with a thickness of 75 μm. This film was then wound into a roll, and roll C1 of the film consisting only of the substrate layer was collected.

[0189] In addition, TOYO-TAC (trade name: M100) manufactured by Toyobo Co., Ltd. was fed into an extruder and cooled and solidified on a casting drum with a surface temperature set at 25°C to produce roll A2 of unstretched film.

[0190] Output substrate roll C1, output roll A2 in a way that is bonded to one side, set the heating roller with Teflon tube wound to 160°C, and perform lamination while clamping to form single-sided bonded roll C2.

[0191] Further output single-sided lamination roll C2, which is output in such a way that roll A2 is laminated to the substrate layer side. Similarly, lamination is performed while clamping to obtain a roll of thermally fusible laminated oriented film. The characteristics of the thermally fusible laminated oriented film obtained by this method are summarized in Table 1.

[0192] [Comparative Example 5]

[0193] In Example 1, the stretch ratio was set to 3.8 times in the length direction and 4.2 times in the width direction, and the relaxation rate was reduced to 1%. Otherwise, rolls of thermally bondable laminated oriented films were obtained in the same manner as in Example 1. The characteristics of the obtained thermally bondable laminated oriented films are summarized in Table 1.

[0194] [Comparative Example 6]

[0195] In Example 1, resin A was replaced with a resin made of 100% by mass of 6 nylon, and otherwise the same procedure was followed as in Example 1 to obtain rolls of thermally bondable laminated oriented films. The properties of the obtained thermally bondable laminated oriented films are summarized in Table 1.

[0196] [Comparative Example 7]

[0197] In Example 2, resin B was replaced with a resin made of 100% by mass of polymethylpentene. Otherwise, the procedure was the same as in Example 2 to obtain rolls of thermally bondable laminated oriented films. The properties of the obtained thermally bondable laminated oriented films are summarized in Table 1.

[0198] [Table 1]

[0199]

[0200] As shown in Table 1, in Examples 1-8, it is possible to obtain thermally fused laminated oriented films with sufficient mechanical properties, high durability under humid and hot conditions and high adhesion at the laminated interface, and good bonding state during thermal bonding.

[0201] In contrast, in Comparative Example 1, where the substrate layer was heat-laminated on both sides after biaxial stretching, the adhesion between the substrate layer and the interface was insufficient. Furthermore, in Comparative Example 2, where only one side was heat-laminated, the adhesion between the substrate layer and the interface was also insufficient. Because only one side was laminated, residual stress existed only on one side of the substrate layer and adhesive layer, resulting in poor durability under humid and hot conditions.

[0202] On the other hand, in Comparative Example 3, where no stretching was performed after co-extrusion, the mechanical properties became insufficient, and the adhesion of the laminate interface also decreased. In Comparative Example 4, where a heat-bonded layer was directly heat-laminated using a polyester substrate, the durability under humid and hot conditions was poor, and the adhesion of the laminate interface also decreased. Furthermore, in Comparative Example 5, where the heat distortion rate at 150°C exceeded 4%, the bonding condition during heat bonding deteriorated. Moreover, in Comparative Examples 6 and 7, where the substrate layer did not contain modified polyolefin resin, the adhesion of the laminate interface also decreased, and there were also items where the decrease in adhesion was significant and could not be evaluated.

[0203] Industrial availability

[0204] The thermally bondable laminated oriented film of the present invention exhibits excellent adhesion to various planar or film-shaped adherends such as resins without peeling between layers, regardless of whether it contains glass or fibers, primarily metals, for reinforcement. It also demonstrates strong durability even under severe durability evaluations. Furthermore, by maintaining the rigidity of the substrate layer to withstand the heat during bonding, it can suppress bonding defects. Therefore, it has high potential for industrial application.

Claims

1. A heat-melting laminated oriented film, wherein a heat-melting layer containing a heat-melting polyolefin resin is disposed on two sides of a substrate layer formed of a resin composition in direct contact via co-extrusion, said resin composition comprising 99.9–60% by weight of polyamide resin or polymethylpentene resin and 0.1–40% by weight of modified polyolefin resin. With the length direction defined as the X-axis, the width direction as the Y-axis, and the thickness direction as the Z-axis, stretching orientation was performed at least along one of the X-axis or Y-axis directions. The heat deformation rate is less than 4% when heat-treated in a constant temperature bath set at 150°C for 30 seconds in both the X and Y axes.

2. The thermally weldable laminated oriented film according to claim 1, wherein, In at least one direction of the X-axis or Y-axis, the energy storage modulus at 150℃ is above 50MPa, and the fracture strength is above 50MPa.

3. The thermally bondable laminated oriented film according to claim 1, wherein, The thickness of the heat-fusion bonding layer disposed on both surfaces is 10 μm or more and 100 μm or less. The birefringence difference between the two surfaces of the thermally bondable layer is less than 0.0001.

4. The thermally weldable laminated oriented film according to claim 1, wherein, Orientation is achieved through successive or simultaneous biaxial stretching along both the X and Y axes.

5. The thermally weldable laminated oriented film according to claim 1, characterized in that, The resin composition contains 85-65% by mass of polyamide resin and 15-35% by mass of modified polyolefin resin, wherein the modified polyolefin resin is modified polypropylene resin, the relative viscosity of the polyamide resin measured in 96% sulfuric acid is 2.4-3.2, and the acid value of the modified polypropylene resin is 1.0-3.5 mgKOH / g.

6. The thermally weldable laminated oriented film according to claim 1, wherein, The heat-melting polyolefin resin is a mixture of multiple polyolefins with melting peak temperatures of 100°C to 165°C as determined by DSC, modified with anhydride, the anhydride content being 0.1 to 3% by mass, and the MFR being 1 to 30 g / 10 minutes after applying a load of 2.16 kg at 230°C. The extraction amount of low molecular weight components with a number average molecular weight of less than 1000 using acetone is less than 1% by mass.

7. A roll formed by winding a thermally bondable laminated oriented film according to any one of claims 1 to 6 along its length.

Citation Information

Patent Citations

  • Production of pyrazole derivative

    JP1988031468B2

  • Hot-melt adhesive resin film and production method of the same

    JP2017036354A

  • Laminate

    WO2019078134A1

  • Polyamide-based laminated biaxially-stretched film, and vapor-deposited polyamide-based laminated resin film

    CN101835608A

  • Multi-layer laminated body excellent in inter-layer strength

    JP2009083478A